1974
DOI: 10.1007/bf01219534
|View full text |Cite
|
Sign up to set email alerts
|

Sex related diurnal variations in venous blood glucose and plasma insulin levels effects of estrogens in men

Abstract: Summary. Significant sex differences were observed in 24 young lean men and women submitted to two mixed isocMorie meals (880 KcM; protein 40 g; carbohydrate 90 g; fat 40 g;) at 8.15 AM and 12.45 PM. After an overnight fast venous blood glucose levels were lower in women than in men. Plasma insulin responses were lower after the afternoon meal than after the morning one in men bu~ not in women. Thus women did not present the well known cycle of insulin secretion described in men. Estradiol benzoate, 10 mg per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Many authors reported that, in fasting conditions, there is a smaller resting glucose concentration in women compared to men (Hautecouverture et al 1974;Selmi et al 1976;Tchobroutsky 1991). In the present study, the carbohydrate ingestion during breakfast was the same in both sexes, since all subjects ate a standardized breakfast.…”
Section: Discussionmentioning
confidence: 95%
“…Many authors reported that, in fasting conditions, there is a smaller resting glucose concentration in women compared to men (Hautecouverture et al 1974;Selmi et al 1976;Tchobroutsky 1991). In the present study, the carbohydrate ingestion during breakfast was the same in both sexes, since all subjects ate a standardized breakfast.…”
Section: Discussionmentioning
confidence: 95%
“…Fasting glycaemia is lower in pre-menopausal women than in men [13,16] (Table 2). We have also shown that natural oestrogen administration decreases fasting blood glucose levels in young healthy men [17].…”
mentioning
confidence: 54%
“…Results were subanalysed by gender, because of known gender differences in carbohydrate intake, 2 and glucose. 1,4,5 Mean fasting glucose was lower in women (5.1 mmol/L) than men (5.3 mmol/L), P ¼ 0.03. There were no significant gender differences for age (t ¼ À1.20, P ¼ 0.23), postprandial glucose (t ¼ À1.98, P ¼ 0.051) or prandial change in glucose (t ¼ À1.23, P ¼ 0.22).…”
Section: Resultsmentioning
confidence: 99%
“…2 Although the exact timing of the postprandial venous plasma glucose nadir is unknown, other studies would suggest that it is around 90 min with the maximal capillary-venous glucose difference occurring at one hour. 4,5,8 Alternative methods of glucose measurement such as continuous glucose monitoring of interstitial glucose (CGM) are unfortunately unlikely to define the exact timing of the nadir, due to the complex relationship between glucose concentrations within the capillary, venous and interstitial compartments. 9 In addition, although CGM results are thought to reflect venous glucose concentration, especially under stable conditions, 9 CGM calibration is usually undertaken using a capillary sample measured with a glucose meter, thus introducing an element of incorporation bias into the CGM results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation